Ethnographic study of ethnoparenting practies in the Samin community of Jepang village - Ismawati, Putri (Thufuli, 2025)
This qualitative research, conducted in Jepang Village, Margomulyo District, Bojonegoro Regency, aims to describe the ethnoparenting process and character education values within the Samin community. Using an ethnographic approach, data collection involved observation, interviews, and literature review. Interactive analysis revealed that Samin ethnoparenting practices are rooted in Surosentiko Samin's teachings, emphasizing five principles such as laku jujur, sabar, trokal, lan nrimo (being honest, patient, persistent, and accepting destiny); aja dengki, srei, dehwen kemeren, pekpinek barange liyan (do not be envious, greedy, take advantage of others, or steal someone else's property); ojo mbedo mbedakne sapodo padaning urip (don't judge people based on their life situations; everyone is family); ojo waton omong, omong sing gawe waton (talking is more than simply being able to speak; you must also be able to prove it); biso roso rumongso (implies feeling positive or having a good assumption about everyone). Ethnoparenting practices encompass five stages: pregnancy, childbirth, infant care, school-age care, and adolescence. Character education employs role-modeling and habituation. This study contributes to understanding Samin cultural parenting practices and their significance in shaping children's character. These findings contribute to the integration of indigenous parenting models into character education frameworks.